Learn to write numbers: 1,2,3 : reusable wipe-off pages - Barry, Norwahldah (Freeport, NY : Pen Notes, Inc, 1987)
Teaches children to write numbers the easier way using four simple party shapes. Ages 3 and up.
Keywords: Handwriting